An IoT-Based Monitoring System For Assessing Biodigester Fertilizer Quality For Vegetable Farmers - Yusran Yusran; Alex Ferdinal; Anjun Dermawan (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose: The increasing demand for organic vegetables is due to their superior quality, freshness, longer shelf life, and healthier flavors compared to non-organic vegetables. Organic vegetables are generally considered safer for consumption. Therefore, vegetables with higher nutritional content, such as vitamin C, antioxidants, and rich minerals, as well as fresher colors and appearance, are sought after. Methodology: This Internet of Things Monitoring System research was implemented and developed using the waterfall method. . Results The results of the reading from the Node MCU control device will then be sent via a WiFi device so that the results can later be accessed online. Findings: Conditions in the field for vegetable farmers make it difficult to use appropriate biodegradable fertilizers, therefore farmers tend to use more instant fertilizers because they are easier and more practical, where fertilizers and pesticides can be purchased at shops.Novelty: The system equipment used and developed is sensor equipment designed to obtain information related to the quality of Biodigester fertilizer that is suitable for use as vegetable fertilizer, namely a methane sensor (MQ-4 Sensor) and a control device used by the MCU Node. Originality: This research uses the Waterfall method, the stages are Engineering, design and implementation, testing, application and maintenance. Conclusion: The test results of the prototype of the cow manure pH meter as a biodigester fertilizer above show that the NodeMCU-based cow manure pH meter system was successfully designed and functioned well. The pH value can be displayed on the LCD and sent to a smartphone in real time via a WiFi network. The measurement accuracy is quite good with an error below 3%. Type of Paper: Empirical Research Articles